Evaluation of the soft-tissue changes in orthodontic patients treated using traditional versus miniscrew-supported anchorage - Tarulatha Revanappa Shyagali; Pushpraj Kesharwani; Sarvraj Kohli; Abhishek Gupta; Tanvee Tiwari; Ruchi Jha (Wolters Kluwer Medknow Publications, 2020)
Background and the Purpose: Soft-tissue paradigm shift clearly indicates the soft-tissue orientated treatment plan in orthodontics. Hence, the current study was undertaken with the aim to analyze the soft-tissue changes in orthodontic patients who have undergone upper and lower first premolar extractions followed by en masse retraction with conventional anchorage and mini-implant-supported anchorage. Materials and Methods: A retrospective study was done on 32 orthodontic patients with a mean age of 17.5 ± 3.2 years. All the patients had undergone upper and lower first premolar extractions followed by fixed orthodontic treatment and a friction type of orthodontic retraction to close the extraction spaces using NiTi coil springs. All the cases belonged to high anchorage category. The sample was divided into groups, namely Group I (20) treated using conventional anchorage system and Group II (12) treated using implant-supported anchorage. The pre- and posttreatment lateral cephalograms were traced for different soft-tissue parameters such as mentolabial angle, nasolabial angle, liner measurements from E line, H line and Burstone's subnasale to pogonion line. Results: Significant changes were seen between the pre- and posttreatment soft-tissue parameter values for both Group I and Group II. However, Group II showed more changes in relation to superior sulcus to E line (SS-E line), Ls-E line, Li-E line, mentolabial angle, Ls-SnPg, Li-SnPg, Li-H line, and H line to nose tip, and the changes were statistically significant (P ≤ 0.05). The comparison of Group I and Group II showed that there existed a significant difference for the parameters such as nasolabial angle, mentolabial angle, and H line to nose tip (P ≤ 0.05). Conclusion: Facial soft-tissue changes were to a greater extent in patients who have undergone implant-supported orthodontic retraction of anterior teeth in comparison to the conventional retraction method.